UNMASKING PRIMARY ALDOSTERONISM IN A PATIENT WITH END STAGE RENAL DISEASE: A CASE REPORT - Jasmiad, Nurbadriah; See, Chee Keong; Shudim, Saiful Shahrizal; Ismail, Ilham (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Managing hypertension in a patient with end-stage renal disease (ESRD) requires a combination of antihypertensive medications and volume control. It is common to encounter refractory hypertension in ESRD. Investigation of primary aldosteronism (PA) as a cause of refractory hypertension in ESRD is potentially difficult. These patients are on multiple antihypertensive medications that cannot be discontinued, thus complicating the interpretation of aldosterone-renin ratio. CASE We present a patient with ESRD on peritoneal dialysis with refractory hypertension and hypokalaemia investigated for primary aldosteronism. The patient is a 72-year-old male, known hypertensive for 40 years, with poorly controlled blood pressure for the past 20 years. The presence of refractory hypertension and hypokalaemia prompted an investigation for primary aldosteronism ten years ago, where the patient tested negative. Over the next ten years, his eGFR deteriorated, and he was initiated on peritoneal dialysis a year ago. Despite peritoneal dialysis, his BP remained poorly controlled while on six antihypertensive medications, including furosemide and spironolactone. Despite being on six confounding antihypertensive medications, his plasma aldosterone was not suppressed and instead, elevated at 1229 pmol/L with a normal direct renin level (9 mU/L). Adrenal CT revealed bilateral adrenal adenomas. Further assessment with adrenal vein sampling was done. Surgery was explored, but the patient was not keen. Spironolactone dose was optimized which led to improvement of blood pressure control and reduction of other antihypertensive medication doses without occurrence of hyperkalemia. CONCLUSION In a highly suspicious case of primary aldosteronism, a repeat screening test is warranted to prevent missing the diagnosis. Performing screening tests for PA in ESRD can be attempted but expect complexity in interpretation. Spironolactone can be given with caution in ESRD patients with PA.